Graphene enhances the loading capacity and lubrication performance of ionic liquids: a molecular dynamics study - Jiang, Haodong (2023)
Ionic liquid (IL) combined with graphene additives have garnered extensive attention in the field of high-performance lubricating materials. However, the ambiguous mechanism of graphene influencing the load-carrying and anti-wear capacity of ILs needs further study. In this work, friction simulation shows that adding graphene causes friction coefficient to reduce by up to 88% compared with pure ILs, but lubrication performance is lost due to the destruction of graphene under high stress. Meanwhile, multilayer graphene has better friction-reducing performance and friction durability as compared to the monolayer structure, which is attributed to the easy-shear property and the reduction in the percentage of high tensile stress sites in multilayer graphene structure. In addition, it was found that excessively thick ILs film would form a three-body abrasive wear structure with graphene, which accelerated the structural destruction of graphene and caused a decline in its tribological properties. It is believed these findings can be valuable for designing of high-performance lubricating oil for practical engineering.